Attitude Changes among Science Teachers during a Statewide Institute Program. - Zurhellen, Joan H.; Johnson, Clayton H. (Science Education)
The article focuses on investigated attitude changes among participants involved in an in-service institute centering on a curricular change in science. It was an assumption of the study that behavior change must be preceded or accompanied by attitude change. One researcher pointed out that on-high decision making will not accomplish educational change and advocated involving teachers in activities that will change their outlooks, perceptions and attitudes. The statewide in-service institute comprised eight separate local institutes in different sectors of the state. The attitudes investigated were those toward students, toward youth and typical classroom situations, toward educational innovation, and toward self-real and ideal, ideal teacher and ideal student.